The Effect Of Using Abacus Media On Students' Ability In Arithmetic Operations On The Addition Of Whole Numbers - Kudus Kudus (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2023)
Mathematics is essential since its application cannot be separated from our daily lives. Moreover, mathematics can also develop an awareness of essential values. Arithmetic operations are one of the mandatory topics in mathematics education at the elementary school level. Addition and subtraction of tens and hundreds are taught in Grade 1 of elementary school. In this grade, mathematics serves as the initial process for students to learn arithmetic operations, which are part of mathematical skills. Counting activities in a simple context have been introduced before students enter elementary school age. However, the abstract nature of mathematics makes it difficult for many students to learn. This phenomenon is evident in the low arithmetic skills of students, as reflected in the low average scores for mathematics, especially in the arithmetic topic.